Exercise Snacking to Improve Muscle Function in Healthy Older Adults: A Pilot Study - Oliver J. Perkin; Polly M. McGuigan; Keith A. Stokes (Journal of Aging Research)
Loss of muscle mass and strength are seemingly accepted as part of the ageing process, despite ultimately leading to the loss of independence. Resistance exercise is considered to be primary defence against loss of muscle function in older age, but it typically requires access to exercise equipment often in a gym environment. This pilot study aimed at examining the effect of a 28-day, unsupervised home-based exercise intervention on indices of leg strength and muscle size in healthy older adults. Twenty participants were randomly assigned to either maintain their habitual physical activity levels (Control; n=10; age, 74 (5) years; body mass, 26.3 (3.5) kg/m2) or undertake “exercise snacks” twice daily (ES; n=10; age, 70 (4) years; body mass, 25.0 (3.4) kg/m2). Both groups consumed 150 g of yogurt at their breakfast meal for the duration of the intervention. Sixty-second sit-to-stand score improved by 31% in ES, with no change in Control (p<0.01). Large effect sizes were observed for the difference in change scores between the groups for interpolated maximum leg pressing power (6% increase in ES) and thigh muscle cross-sectional area (2% increase in ES). The present pilot data suggest that exercise snacking might be a promising strategy to improve leg muscle function and size in older adults and that further investigation into zero-cost exercise strategies that allow high frequency of training is warranted.